(untitled) (Heritage, 2021)
The Women’s Branch in Gnjilane was a humanitarian-educational organization, which operated intermittently from 1914 to 1941 in the area of Gnjilane and its surroundings. At the meeting held on March 2, 1914. in Gnjilane, the Women’s Branch and its Women’s Craft School were established at the same time. The main goal, and at the same time the reason why they were formed, was to work, above all, in the educational, humane, but also in the national and economic field. The work of the Branch was mostly related to vocational education and upbringing of female children, school work, management, financing, charitable and humanitarian activities. Taking into account that the material and financial assistance from the state was insufficient, the Branch collected donations in the form of money and products from its members, parents and citizens. Also, the mentioned Branch organized events and parties from where the income went for the needs and support of the school itself. The students who graduated from these schools had the opportunity to successfully perform craft jobs and thus be more advanced in contributing to the formation of a new, modern society.